Local visitors’ willingness to pay for an increase in the entrance fee at Chengdu Research Base of Giant Panda (Ailuropoda melanoleuca) breeding, China - Yingyi, Peng; Matthew, Nitanan Koshy; Mzek, Tareq (SAGE Publications, 2025)
The wild giant panda population has increased to 1,864 and its status has been updated from endangered to vulnerable. This attests to China’s fruitful efforts in wildlife conservation and the promotion of biodiversity. However, existing evidence implies that additional financial support is crucial to support giant panda conservation endeavors. This study aimed to (i) determine the local visitors’ level of knowledge, awareness, and attitude toward the giant panda conservation, (ii) identify the factors influencing local visitors’ willingness to pay (WTP), and (iii) estimate local visitors’ WTP for an increase in the entrance fee at Chengdu Research Base of Giant Panda Breeding (CRBGPB). The study utilized the contingent valuation method (CVM) based on double-bounded dichotomous choice (DBDC) technique to elicit the respondents’ WTP. The results revealed a high level of awareness and positive attitude among respondents about giant pandas and the significance of their conservation. The age, gender, knowledge, awareness, and attitude are key factors that influence WTP among local visitors. The estimates indicate that respondents’ WTP for an increase in entrance fees ranged from CNY 29.38 to CNY 37.40 per visit. These findings offer valuable insights for the CRBGPB and stakeholders to devise conservation strategies and pricing policies for giant panda conservation.